ECONOMIC PERFORMANCE OF PODILSKYI 94 AND LVIVSKYI ARTICHOKE VARIETIES - Пую, В. Л. (Podilian Bulletin: Agriculture, Engineering, Economics, 2017)
The paper expounds the parameters of silage; mowing; and tuberous plant productivity of Podilskyi 94 and Lvivskiy artichoke varieties in black soil research fields of entrepreneur O.V Kornik in Kamianets-Podilskyi district; Khmelnitskyi region for 2010-2012. Lvivskiy variety proved more productive as to the yield of the stem mass (570 centner / ha); which exceeded Podilskyi 94 (St) by 17.8% (86 centner / ha); dry matter content by 11.4% (9 centner / ha); feed units by 12.3% (10 centner / ha); and leaf coverage by 22.7%. Over 148 days of active vegetation with the average leaf surface of 38.6 thousand m2 / ha; agrocenosis of the Lvivskiy variety formed the photosynthetic potential of the crop – 5.7 million. m2 × days / ha; by 10.7% more than Podilskyi 94. Increased tillering of the artichoke plants provided three full secured mowings of green mass in the amount of 290-321 centner / ha; the green conveyor system allows its use from 20-25 June to 1-5 July; from 1-5 August to 10-15 August; and from 20-25 September to 1-5 October. Bulb performance of the artichoke with the density of 35-40 thousand plants (snags) for 1 ha was 300- 380 centner / ha. It turned out that Lvivskiy was the better variety that exceeded the 94 Podolsky variety by 11.3% (35 centner / ha); dry matter – 11.1% (9 kg / ha); and fodder units – 12.0% (10 centner / ha).